Optimization of Thermal Management System with Water and Phase Change Material Cooling for Li-Ion Battery Pack - Quanyi Li; Jong-Rae Cho; Jianguang Zhai (Energies, 2021)
The cooling structure of a battery pack and coupled liquid cooling and phase change material (PCM) were designed in a thermal management system to enhance the cooling performance and extend the service life of lithium-ion battery packs. Numerical simulations were conducted based on the finite volume method. This study focuses on factors such as the layout of the terminal, flow rate of the coolant, different sections of the cooling pipe, position of the cooling pipe, and coupled liquid cooling, and investigates their influences on the operating temperature. The results show that a reasonable terminal layout can reduce heat generation inside the batteries. The appropriate flow rate and position of the cooling pipe effectively reduced the maximum temperature and minimized energy consumption. Then, the PCM was placed between the adjacent batteries near the outlet to enhance the uniformity of the battery pack. The temperature difference was reduced to near 5 K. This study provides a clear direction for improving the cooling performance and extending the service life of battery packs.